Printable elastomeric electrodes with sweat-enhanced conductivity for wearables - Lv, Jian (2021)
We rationally synthesized the thermoplastic and hydrophilic poly(urethane-acrylate) (HPUA) binder for a type of printable and stretchable Ag flakes–HPUA (Ag-HPUA) electrodes in which the conductivity can be enhanced by human sweat. In the presence of human sweat, the synergistic effect of Cl− and lactic acid enables the partial removal of insulating surfactant on silver flakes and facilitates sintering of the exposed silver flakes, thus the resistance of Ag-HPUA electrodes can be notably reduced in both relaxed and stretched state. The on-body data show that the resistance of one electrode has been decreased from 3.02 to 0.62 ohm during the subject’s 27-min sweating activity. A stretchable textile sweat-activated battery using Ag-HPUA electrodes as current collectors and human sweat as the electrolyte was constructed for wearable electronics. The enhanced conductivity of the wearable wiring electrode from the reaction with sweat would provide meritorious insight into the design of wearable devices.